Structural characterization of three acidic polysaccharides from Opuntia dillenii Haw. fruits and their protective effect against hydrogen peroxide-induced oxidative stress in Huh-7 cells - Liu, Rui; Chu, Fangxin; Yan, Zheng; Chen, Hanqing (Food science and human wellness, 2024)
Three novel acidic polysaccharide fractions (OFPP-1, OFPP-2, OFPP-3) with different molecular weights (803.7, 555.1 and 414.5 kDa) were isolated from the peeled Opuntia dillenii Haw. fruits by alkali-extraction, graded alcohol precipitation and column chromatography. Structural analysis indicated that OFPPs were pectic polysaccharides consisting of rhamnose, arabinose and galactose residues. The backbone of OFPP-1 consisted of a repeating unit →6-α-D-GalpA-(1→2)-α-L-Rhap-(1→ with T-α-D-GalpA-(1→6)-α-D-GalpA-(1→4)-α-D-Glcp-(1→, T-β-D-Xylp-(1→6)-α-D-GalpA-(1→4)-α-D-Glcp-(1→ or T-α-D-GalpA-(1→3)-α-L-Araf-(1→ as the side chains. The backbone of OFPP-2 consisted of a disaccharide repeating unit →2)-α-L-Rhap-(1→4)-β-D-GalpA-(1→ with T-β-L-Araf-(1→ as the branches substituted at the O-4 position of →2,4)-α-L-Rhap-(1→. Whereas the backbone of OFPP-3 was →2,4)-α-L-Rhap-(1→2)-α-L-Rhap-(1→3)-β-L-Araf-(1→ or →2,4)-α-L-Rhap-(1→2)-α-L-Rhap-(1→4)-β-D-GalpA-(1→, which was branched at the O-4 position of →2,4)-α-L-Rhap-(1→. Moreover, these 3 polysaccharide fractions could protect Huh-7 cells against H2O2-induced oxidative stress to different extents by decreasing the MDA content and increasing the SOD, CAT, GSH-Px activities and the GSH level in the Huh-7 cells. These results suggest that OFPPs have the potential to be used as natural antioxidants. [Display omitted] •Three novel acid polysaccharide fractions are isolated from Opuntia dillenii Haw. fruit.•The compositions and structural features of OFPPs are characterized.•The OFPPs can protect Huh-7 cells against oxidative stress induced by H2O2.